A temporal compatible object relational database system - Vo, Thi Ngoc Chau; Chittayasothorn, Suphamit (My University, 2007)
Time-varying data management has been much taken into consideration with either the tuple(object)timestamping or attribute-timestamping scheme. The first scheme is simpler with first normal form relations; but the second is more expressive and natural with unnormalized tables. However, no existing database management system has supported the handling of attribute timestamping on such unnormalized tables. In addition, even though planned for a long time, standards SQL have not yet been published with any temporal semantics. Moreover, there exists no available environment where both temporal and nontemporal database users work together with different awareness of temporal aspects of a database. Therefore, to facilitate the temporal data management according to users' needs and their own ability in data manipulations, a database system is figured out with several types of database users in this paper. It is a temporal object relational database system following the attribute timestamping scheme, allowing upward compatibility with SQL:2003 and temporal upward compatibility. The implementation is carried out on Oracle 10g without the introduction of any new temporal clauses into SQL:2003. As a result, both temporal and nontemporal database users do not have to make any effort to use this system © 2007 IEEE.
Keywords: Attribute timestamping; Object relational database system; SQL; Temporal database